Dissociative Social Interaction Among Extra-Campus Organizations Of Islamic Students - Ramdani, Alif Melky; Negara, Chandra Perwira; Taufika, Ryan (Journal of Strategic and Global Studies, 2018)
This article aims to explain a study of the factors causing dissociative social interaction among the big three extra-campus organizations of Islamic students in Indonesia, namely HMI, KAMMI and PMII at Padang State University, Indonesia. This study is a result of research using qualitative approach with type of case study research. The research data was collected through in-depth interviews by purposive sampling on leaders and active cadres of the organization and through documentary tracking. The study was compiled using interactive models popularized by Miles and Huberman (reduction, display and conclusion / verification), and analyzed using the Michael Michael Blau social behavioral exchange theory framework. The findings of this study conclude that the factors causing dissociative social interaction in the extra-campus organizations of Islamic students are: (1) low trust between organizations, (2) high motivation to master intra-campus politics, (3) negative assessment of other organizations, (4) can not suppress organizational ego, (5) limited availability of potential cadre candidates and (6) lack of communications at the commissariat level.